MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA MELALUI STRATEGI PERAN POLA ASUH ORANG TUA DI ERA DISRUPSI - Angelica, Prita Laura; Syailendra, Siera (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2024)
This research aims to understand the role of parental parenting in strategies to improve the quality of children's Human Resources (HR) in the era of digitalization. As is known, in this fast-moving digital 4.0 era, it presents new challenges and surprises for every individual human being. As a result of progress in the digital era, it certainly has positive or negative impacts, which everyone will experience difficulties in responding to. In particular, for every parent who will continue to educate their children while adapting to the current digital era. In addition, parents are required to be able to produce and shape their children into individuals who are mature in behavior and character in order to improve the quality and value of Human Resources (HR). This research takes a descriptive qualitative approach, namely understanding, exploring and expanding thinking about a particular phenomenon in a more complex and systematic way. With data and material collection techniques using the Study Literature Review (SLR) method from reputable journals, books and compatible mass media reports. As a result, the parenting patterns of parents in the past were very inversely proportional to the parenting patterns of Generation Z and Millennials today. In ancient times, parents always applied democratic, authoritarian, permissive or neglectful parenting styles in nurturing their children to achieve success. However, in this era of digitalization, these four parenting patterns will not be implemented well and maximally if the role of parents and families is not wise in aligning their parenting patterns well according to the time, situation and condition of the child.